Design, formulation, and evaluation of a herbal gel contains melissa, sumac, licorice, rosemary, and geranium for treatment of recurrent labial herpes infections - Abolfazl Aslani; Behzad Zolfaghari; Yeganeh Fereidani (Wolters Kluwer Medknow Publications, 2018)
Background: The herpes simplex virus is a human pathogen which can cause skin or mucous membrane infections. Melissa, sumac, licorice, rosemary, and geranium have antimicrobial, antiviral, anti-inflammatory, and local analgesic effect. Shortening recovery period of recurrent herpes labialis and control of viral protein formation are the other effects of these herbs. The aim of this study is design, formulation, and evaluation of the gel containing extracts of these five herbs. Materials and Methods: In this experimental study after photochemical and macroscopic evaluation of these medicinal herbs, the semisolid concentrated extracts were incorporated in gel bases. Mucoadhesive gels were prepared using carbopol 940, sodium carboxymethylcellulose (Na CMC) and hydroxypropyl methylcellulose K4M as bioadhesive polymers. Physicochemical tests, viscosity, mucoadhesive strength measurement, and in vitro drug release study were carried out on formulations F10 (carbopol 940, 0.5% and Na CMC, 3%) and F11 (carbopol 940, 1% and Na CMC, 3%). Results: Polyphenol content of extracts mixture was measured 210.8 ± 13.68 mg GAE/g. pH of formulations was 6.0 ± 0.2. 14 gel formulations were prepared. Physical appearance, homogeneity, and consistency of F10and F11were good. Mucoadhesion and viscosity of F11was more than F10. Study of release profiles in F10and F11formulations showed drug release from F11was slower. Conclusion: The best formulation for treatment and shortening recovery period of recurrent labial herpes infections should exhibit high value of mucoadhesion, show controlled release of drug. F11with the highest viscosity and mucoadhesion and the lowest release rate was considered as the best formulation.